AVALIAÇÃO DA ATIVIDADE GENOTÓXICA/ANTIGENOTÓXICA DO LÁTEX DE CROTON URUCURANA USANDO O ENSAIO SMART CLÁSSICO - SILVA, Mathws Rodrigues da; GOUVEIA, Juceli Gonzalez; GUTERRES, Zaira da Rosa; GARCEZ, Walmir Silva; FIGUEIREDO, Patrícia de Oliveira; SOARES, Luzinátia Ramos (ANAIS DO ENIC, 2024)
-